The impacts of physical activity on psychological and behavioral problems, and changes in physical activity, sleep and quality of life during the COVID-19 pandemic in preschoolers, children, and adolescents: A systematic review and meta-analysis - Pang, Johnson C. Y.; Chan, Eric L. S.; Lau, Herman M. C.; Reeves, Kara K. L.; Chung, Tina H. Y.; Hui, Heidi W. L.; Leung, Alfred H. L.; Fu, Allan C. L. (Frontiers in Pediatrics, 2023)
Background: The COVID-19 pandemic has greatly affected the level of physical activity (PA). However, little is known about its effect on health outcomes. Methods: Articles without language restrictions published from the database inception through March 16, 2022, were retrieved using the CINAHL Complete, Cochrane Library, EMBASE, Medline, PubMed, and PsycINFO databases. High-quality articles assessing the effect of PA on psychological and behavioral problems. Additionally, PA, QoL, and/or sleep problems before and during the pandemic were included. Articles without data regarding PA or involving non-general populations were excluded. The PRISMA and MOOSE guidelines were followed. Data quality of the selected articles was assessed using the Newcastle-Ottawa Scale and GRADE approach. Data were pooled using a random-effects model and sensitivity analysis if heterogenicity was high (I2≥50%). The relationship between PA and psychological and behavioral problems; and changes in PA, QoL, and sleeping patterns before and during the pandemic in preschoolers, children, and adolescents were investigated. A meta-analysis was conducted; odds ratios (ORs), mean differences (MD), and standardized MDs (SMDs) were calculated. Results: Thirty-four articles involving 66,857 participants were included. The results showed an overall significant protective effect between PA and psychological and/or behavioral problems (OR=0.677; 95% CI=0.630, 0.728; p-value<0.001; I2=59.79%). This relationship was also significant in the subgroup analysis of children (OR=0.690; 95% CI=0.632, 0.752; p-value<0.001; I2=58.93%) and adolescents (OR=0.650; 95% CI=0.570, 0.741; p-value<0.001; I2=60.85%); however, no data on the relationship in preschoolers were collected. In addition, the overall time spent on PA significantly decreased by 23.2 minutes per day during the COVID-19 pandemic (95% CI=-13.5, –32.9; p-value<0.001; I2=99.82%). Moreover, the results showed an overall significant decrease in QoL (SMD=–0.894, 95% CI=–1.180, –0.609, p-value<0.001, I2=96.64%). However, there was no significant difference in sleep duration during the COVID-19 pandemic (MD=0.01 hours per day, 95% CI=–0.027, 0.225; p-value=0.125; I2=98.48%). Conclusion: During the pandemic, less PA was contributed to poor QoL and sleep quality. However, increases in PA are associated with reduced occurrences of psychological and behavioral problems. Implementing recovery plans to address the health effect of the pandemic is essential.